A Study On The Usefulness Of Cash Flow Statement Presented In The Annual Report To Shareholders In Malaysia - Krishnan, Shamala (2002)
The aim of this study is to the assess the ability to understand the cash flow statement by the Malaysian shareholders and to ascertain whether alternative presentation of cash flow statement such as pictorial methods and graphical display would further e